Fracture Behavior of Ion-Nitrided AISI 4140 Steel in accordance with Variable Applied Current Density - Hyun Jun Park; Bum Soo Kim; Chi Sung Ahn; Kyun Taek Cho; Kyoung Il Moon; Sang Sub Kim (Advances in Materials Science and Engineering)
In this study, the fracture behavior of AISI 4140 low-alloy steel nitrided with respect to the applied current density was investigated. A series of rotary bending fatigue tests were performed with various loads (350, 400, 450, and 500 N) at a constant rotational speed of 2000 rpm. The results show that the increase in the fatigue strength of the steel (up to 35%) strongly depends on the compound layer formed during the nitriding process. In addition, the compressive stress generated by nitrogen-ion bombardment and implantation had an advantageous effect on the substantially enhanced fatigue strength; it acted as a protective layer to secure the surface from any external impact. It was found that fatigue strength is increased with increasing fracture toughness index on the surface on the sample. It had the highest fracture toughness index and fatigue strength at about 0.85 mA/cm2 of applied current. The findings of this study will pave the way for applications in related industries.